2010
DOI: 10.1111/j.1365-2133.2010.09987.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up study of occupational hand eczema

Abstract: In the logistic model, risk factors for the continuation of OHE were a long duration of hand eczema before diagnosis, respiratory atopy, skin atopy, and continuation in the same occupation. Those who ended up changing occupation due to their OHE had a better medical and economic prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
92
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 40 publications
14
92
0
3
Order By: Relevance
“…Risk factors for the continuation of dermatitis were a long duration of hand eczema before diagnosis, respiratory atopy, skin atopy, and continuation in the same job. 55 Discuss with patients the possibility that contact dermatitis may persist and require long term management, even after initial treatment and workplace modifications. 8 …”
Section: What Is the Prognosis?mentioning
confidence: 99%
“…Risk factors for the continuation of dermatitis were a long duration of hand eczema before diagnosis, respiratory atopy, skin atopy, and continuation in the same job. 55 Discuss with patients the possibility that contact dermatitis may persist and require long term management, even after initial treatment and workplace modifications. 8 …”
Section: What Is the Prognosis?mentioning
confidence: 99%
“…There are several studies looking at the awareness and level of knowledge in CHE patients or in occupations with high risk for developing hand eczema (17)(18)(19)(20). A common approach of these studies is the use of questionnaires to investigate the level of perception of the disease as well as the knowledge of prevention in cohorts especially at risk, such as hairdressers (17) and health care workers (18,19).…”
mentioning
confidence: 99%
“…A follow-up study over 15 years revealed a chronic disease course in 28% of hand eczema patients [4]. In patients with occupational hand eczema, only 28-40% reported total recovery [5,6]. Poor prognosis and persistence of hand eczema have been found to be correlated with severe initial disease and its duration before diagnosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with occupational hand eczema, only 28-40% reported total recovery [5,6]. Poor prognosis and persistence of hand eczema have been found to be correlated with severe initial disease and its duration before diagnosis [6,7]. In European countries, skin diseases are among the top three in the list of occupational diseases [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation